The eclogite facies gneisses of the Cabo Ortegal Complex (NW Iberian Massif): Tectonothermal evolution and exhumation model - Albert, R.; Arenas, R.; Sánchez-Martínez, S.; Gerdes, A. (Journal of Iberian Geology, 2012)
The tectonothermal evolution of the eclogite facies gneisses of the Cabo Ortegal Complex has been investigated using new field and petrologic studies. This gneissic unit is included in the high-pressure and high-temperature (HP-HT) upper units of the allochthonous complexes of NW Iberia, a Cambrian arc-derived peri-Gondwanan terrane emplaced above ophiolitic units considered to represent the Rheic Ocean suture. Two detailed cross-sections performed in excellent exposures on the Cantabrian coast allows a clear understanding of the lithological constitution and deformations affecting the unit. The eclogitic gneiss unit is constituted by metasedimentary gneisses with abundant mafic inclusions, felsic rocks and rare ultramafic inclusions. The felsic rocks range from centimetric leucosomes to metric bodies and most of them were generated during extensive partial melting affecting the unit. The first tectonic fabric detected in the unit is a rarely preserved S1 foliation developed during subduction (ca. 400-390 Ma; 22 kbar). A drastic and fast exhumation (ca. 390 Ma; 12-10 kbar) generated a regional mylonitic foliation which represents the most prominent structural feature in the HP-HT upper units. The consecutive generation of extensional detachments, recumbent folds and a basal thrust occurred during the change from continental-type subduction to the underthrusting of ophiolitic units. These consecutive structures are probably related and the consequence of a long and pronounced exhumation of the subducted complex. The tectonothermal evolution of the eclogite facies gneisses of the Cabo Ortegal Complex represents an illustrative example of the intricate history of these deeply subducted units, which are relatively frequent in the suture zone of the Variscan Belt. It is important to remark that the structural, metamorphic and geochronological patterns in the evolution of this gneissic unit follows almost perfectly the predictions based in numerical experiments about the exhumation of ultra-high-P complexes. Consequently it represents a direct confirmation of these models.